PERBANDINGAN MOTIVASI PENGGUNAAN MODERN DRESSING PADA PENDERITA ULKUS DIABEKTIKUM DI KELURAHAN KALIJIRAK DAN KELURAHAN WONOLOP O KECAMATAN TASIKMADU KARANGANYAR - Budi Kristanto; Nur Cahyo Saputro; Elga Firdian Candra (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2015)
ABSTRACTIntroduction: The increasing prevalence of diabetes in the world led to an increase in cases of amputation due to diabetes complications. Epidemiological studies reported more than one million amputations are performed on people with diabetes each year. Therefore, prevention and appropriate management of lesions of the foot is the most important thing. The development of wound care is growing very rapidly in the world of health.Objective: This study aimed to compare the motivation of the use of modern dressings in patients with diabetic ulcers in the Wonolopo and Kalijirak villagedistrict of Karanganyar.Methods: This study is a comparative analytical study design to compare the motivation of the use of modern dressings in patients with diabetic ulcers in the Wonolopo and Kalijirak village district of Karanganyar.Respondents: The study sample was taken from the population of people who have diabetic ulcers in the Village Kalijirak as much as 20 and as many as 20 Wonolopo village.Results: Based on the results of independent sample t test with SPSS for Windows series 18 with Î± = 5% (0.05), obtained p equal to 0825 which means p> 0.05 it indicates that Ha is not accepted, which means there is no difference in motivation to use modern dressings in patients with diabetes mellitus with diabetic ulcers among respondents in the Village and Village Wonolopo Kalijirak.Keywords: Motivation, Modern dressings, Wound care